2006
DOI: 10.1177/001440290607200206
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics Instructional Practices and Assessment Accommodations by Secondary Special and General Educators

Abstract: A nationwide random sample of 179 secondary general education math and special education teachers completed a survey asking them about their use of specific instructional practices to help teach math to students with learning disabilities (LD) and emotional/behavioral disorders (EB/D) and their use of specific assessment accommodations with these students. Although general education teachers were generally more knowledgeable about higher level mathematics content (e.g., algebra) than special education teachers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
82
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(94 citation statements)
references
References 20 publications
9
82
1
2
Order By: Relevance
“…A total of eight studies were located through this procedure for inclusion in this synthesis (DeBettencourt, 1999;DeSimone & Parmar, 2006;Fletcher, Bos, & Johnson, 1999;Leyser & Tappendorf, 2001;Maccini & Gagnon, 2006;Minke, Bear, Deemer, & Griffin, 1996;van Hover & Yeagar, 2003;Vaughn, Reiss, Rothlein, & Hughes, 1999). Findings were consistent with the previous synthesis (Scott et al, 1998) and revealed that teachers perceived the majority of instructional adaptations to be highly desirable and somewhat feasible, but reported being only fairly confident, prepared, and supported to implement instructional adaptations in their classroom.…”
Section: Studies To Determine the Effectiveness Of Instructional Adapsupporting
confidence: 53%
“…A total of eight studies were located through this procedure for inclusion in this synthesis (DeBettencourt, 1999;DeSimone & Parmar, 2006;Fletcher, Bos, & Johnson, 1999;Leyser & Tappendorf, 2001;Maccini & Gagnon, 2006;Minke, Bear, Deemer, & Griffin, 1996;van Hover & Yeagar, 2003;Vaughn, Reiss, Rothlein, & Hughes, 1999). Findings were consistent with the previous synthesis (Scott et al, 1998) and revealed that teachers perceived the majority of instructional adaptations to be highly desirable and somewhat feasible, but reported being only fairly confident, prepared, and supported to implement instructional adaptations in their classroom.…”
Section: Studies To Determine the Effectiveness Of Instructional Adapsupporting
confidence: 53%
“…At the secondary level, Maccini and Gagnon (2006) found that special education teachers used assessment accommodations more frequently than general education teachers did, and the total number of methods courses taken predicted teacher use of assessment accommodations. Aside from the frequency they provided accommodations, general educators reported using the same accommodations as special educators.…”
Section: Accommodationsmentioning
confidence: 95%
“…However, studies comparing general and special education teachers' beliefs and practices regarding the instruction of students with special education needs have reported mixed findings. The results of one set of studies suggest that special education teachers are more likely than general education teachers to adapt instruction and use effective behavior management approaches (e.g., Blackorby et al 2004;Maccini and Gagnon 2006). For example, Buell et al (1999) examined general and special education teachers' need for further training in various skills such as making instructional adaptations, managing behavior, and creating individualized education plans.…”
Section: Relations Between Teacher Role and Instructional And Behaviomentioning
confidence: 99%